Book of proceedings of the 2nd Machakos University Annual International Conference - Machakos University (Machakos University Press, 2019)
After successfully hosting the 1st International Conference in April 2018, we organized our 2nd International Conference with great enthusiasm pivoted on the lessons learnt earlier. I am therefore filled with joy to welcome you to read this Book of Proceedings of the conference. As you are aware, the theme of the Conference was “Supporting Green Growth and Knowledge Economy through Research, Innovation and Technology for Sustainable Development,” and this underscored Machakos University’s inherent efforts to the realization of Sustainable Development while being conscious of the environmental implications. Accordingly therefore, the Book of Proceedings has been organized according to the Conference sub-themes as follows: 1. Agriculture, Food and Nutrition Security 2. Health care, Leisure and Tourism Innovation 3. Language, Culture, Social Equity and Governance 4. Built Environment and Infrastructure Development, Industrialization: Emerging Technologies, Manufacturing & Agro- processing 5. Energy, water, climate Change and Environmental Sustainability . Mathematics, Statistics & Data Science, Basic and Applied Sciences 7. Issues in Education and Training 8. Business, Entrepreneurial Innovation, SMEs & Marketing